The Impact of Urban Roughness on Outdoor Thermal Comfort in Hot Arid Climate - Hassan, Susan Abed; Abdul Lateef , Zainab Abdul Kareem (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2024)
The proportion of the world's population living in cities is rapidly increasing, presenting new challenges to the urban environment and quality of life. Among these challenges is the urban environment's impact on residents' outdoor thermal comfort, which can affect their health and well-being. Urban roughness, which includes building and street heights, has a significant impact on the thermal environment of urban areas. Changes in these factors cause variations in temperature distribution, wind speed, and humidity, which affect how people perceive thermal conditions. The research problem is the effect of urban roughness on outdoor thermal comfort in hot arid climate, specifically the height of buildings and the density, for a case study in (Al-Bab Al-Sharqi) in Baghdad city. Measurement method that employed the computer programs (Rino8 and Grasshopper) to calculate the thermal comfort index (UTCI) and its impact on various climatic variables. The findings revealed that the thermal comfort index and the climatic factors associated with it vary depending on the configuration of buildings.